WozARd: A Wizard of Oz Method for Wearable Augmented Reality Interaction—A Pilot Study - Günter Alce; Mattias Wallergård; Klas Hermodsson (Advances in Human-Computer Interaction)
Head-mounted displays and other wearable devices open up for innovative types of interaction for wearable augmented reality (AR). However, to design and evaluate these new types of AR user interfaces, it is essential to quickly simulate undeveloped components of the system and collect feedback from potential users early in the design process. One way of doing this is the wizard of Oz (WOZ) method. The basic idea behind WOZ is to create the illusion of a working system by having a human operator, performing some or all of the system’s functions. WozARd is a WOZ method developed for wearable AR interaction. The presented pilot study was an initial investigation of the capability of the WozARd method to simulate an AR city tour. Qualitative and quantitative data were collected from 21 participants performing a simulated AR city tour. The data analysis focused on seven categories that can have an impact on how the WozARd method is perceived by participants: precision, relevance, responsiveness, technical stability, visual fidelity, general user-experience, and human-operator performance. Overall, the results indicate that the participants perceived the simulated AR city tour as a relatively realistic experience despite a certain degree of technical instability and human-operator mistakes.